The Analysis of Problem-Solving Flow Rate Materials during the Pandemic Era in Elementary Schools from the Teacher's Perspective - Dwi Kurniasih; Wahyudin Wahyudin (Teknodika, 2022)
Learning mathematics during the pandemic at the elementary school level reaped various kinds of problems. This study, therefore, aimed to analyze the teacher's obstacles and types of student errors often made in solving problems with flow rate material during the pandemic from the teacher's point of view. The respondents were 16 elementary school teachers for fifth grade in all Cipeucang Sub-district, Pandeglang Regency, Banten Province. Through a quantitative approach with a survey method, data were collected in the form of a questionnaire via google form. The indicators on the instrument covered two aspects: teacher's obstacles and student errors according to the teacher's perspective. The indicators of teacher obstacles were viewed from learning tools, including methods, media, teaching materials, classroom management, and learning assessment. Meanwhile, the indicators of student error were considered from the four stages of George Pólya's method: the stage of understanding the problem, developing a plan, implementing the planning, and reviewing answers. The data were then processed with the Microsoft Excel application and analyzed by descriptive statistics. The results showed that determining the learning method was an obstacle teacher experienced, and students often made mistakes when making plans, implementing plans, and reviewing answers. These results could be taken into consideration by other researchers to find methods, models, or learning strategies that could minimize the elementary school students’ errors in working on problem-solving on flow rate material.